A Model of Contemporary Philosophies Used in a Science Teacher Education Program. - Sonnier, Isadore L. (Science Education)
The article reports on a model of contemporary philosophies and psychological structures that has evolved as a result of expressions of participants in the National Science Foundation programs on earth sciences at the University of Southern Mississippi, in Hattiesburg, Mississippi. One of the basic assumptions of the model is that individual differences are the sacred rights of different individuals. Fundamental and divergent philosophies, including the underlying psychological structures, can be presented as a "normal curve" expressing a centrally oriented peak of the population count. Four systems of individual beliefs illustrated in the model were compared to the earlier model of philosophical and psychological structures in education.